Henry Thomson, (2024), Who Watches the Watchers. Communist Elites, the Secret Police and Social Order in Cold War Europe. Cambridge: Cambridge University Press. 339 pp - Mihaela TEODOR (Romanian Intelligence Studies Review)
Henry Thomson, an accomplished political economist expert specializing in economic development and political transitions, published earlier in 2024, at Cambridge University Press its latest volume Who Watches the Watchers. Communist Elites, the Secret Police and Social Order in Cold War Europe, which is a compelling exploration of the “guardianship dilemma in authoritarian regimes”, as other reviewers stated.